Intellectual Capital Effect, Financial Performance, and Firm Value: An Empirical Evidence from Real Estate Firm, in Indonesia - Deniswara, Kevin; Uyuun, Ratu Marwaah Firhatil; Lindawati, Ang Swat Lin; Willnaldo, Willnaldo (Journal the Winners: Economics, Business, Management, and Information System Journal, 2019)
This research aimed to analyze the impact of intellectual capital towards the firm’s financial performance and firm’s value. Intellectual capital was measured by Value Added Intellectual Capital (VAIC) which has three components, such as Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA). Firm’s financial performance and firm’s value were measured by Return on Assets (ROA), Return on Equity (ROE), Revenue Growth (RG), and Tobin’s Q ratio. There were 102 observations of Property and Real Estate company sector listed in Indonesia Stock Exchange period 2014-2016 that was analyzed using the linear regression method. The results show that VAIC has a significant impact towards financial performance and firm’s value, except revenue growth, which means that the firm’s ability to generate value added and also profit with total assets and equity increase if IC is managed properly. Therefore, VACA is the only component of VAIC that has a significant impact towards financial performance and firm’s value, except RG which means that the capital employed is already managed properly.